2005
DOI: 10.1111/j.1440-1827.2005.01882.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ABCA7‐positive cells in salivary glands from patients with Sjögren's syndrome

Abstract: ABCA7 is a member of the subfamily A of adenosine triphosphate-binding cassette (ABC) proteins, and highly homologous to ABCA1, which mediates the release of cellular cholesterol and phospholipid to form high-density lipoprotein. ABCA1 and ABCA7 contain two large extracellular domains, ECD1 and 2, which are thought to be important for their functions. Interestingly, part of ECD1 of ABCA7 is deposited as an autoantigen of Sjögren's syndrome. To determine the relationship between ABCA7 and Sjögren's syndrome, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…ABC, ATP-binding cassette transporter; ApoA, apolipoprotein A; CytD, cytochalasin D; KO, knockout. cells were detected in plasma cells from the salivary glands of patients with Sjögren's syndrome ( 41 ). The incidence of single nucleotide polynucleotide allele of HA1 was different between Sjögren syndrome patients and control patients ( 42 ).…”
Section: Discussionmentioning
confidence: 93%
“…ABC, ATP-binding cassette transporter; ApoA, apolipoprotein A; CytD, cytochalasin D; KO, knockout. cells were detected in plasma cells from the salivary glands of patients with Sjögren's syndrome ( 41 ). The incidence of single nucleotide polynucleotide allele of HA1 was different between Sjögren syndrome patients and control patients ( 42 ).…”
Section: Discussionmentioning
confidence: 93%
“…These factors are highly conserved in mouse and human and are expressed predominantly in the hematopoietic tissues; ABCA7, in fact, is highly expressed in the peripheral leukocytes, thymus, spleen, and bone marrow (9,13,17). ABCA7 was also identified as the autoantigen SS-N, an epitope of the autoimmune disease Sjö gren's syndrome (41), and ABCA7-positive cells were identified in salivary glands of the patients (42). The ABCA7 gene is juxtaposed to HA-1, which is causatively linked to graft-versus-host disease after allogeneic stem cell transplantation (43), in close proximity on chromosome 19p13.3 (22).…”
Section: Discussionmentioning
confidence: 98%
“…Studies on SNPs in the HA‐1 gene demonstrated that the incidence of an allele (168 His) was lower in the patients with Sjögren's syndrome than controls [16]. In addition, SS‐N is a part of the first extracellular domain of ABCA7 [13] and an antibody against this domain reacted to infiltrating plasma cells in salivary glands from the patients of this disease, but not in those from non‐specific sialoadenitis patients [17]. The pathophysiological significance of these observations is unclear to date.…”
Section: Clinical Relevance and Gene Disruptionmentioning
confidence: 95%